2019
DOI: 10.1371/journal.pone.0222598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with bacterial translocation in Japanese patients with type 2 diabetes: A retrospective study

Abstract: ObjectiveTo explore clinical factors associated with bacterial translocation in Japanese patients with type 2 diabetes mellitus (T2DM).MethodsThe data of 118 patients with T2DM were obtained from two previous clinical studies, and were retrospectively analyzed regarding the clinical parameters associated with bacterial translocation defined as detection of bacteremia and levels of plasma lipopolysaccharide binding protein (LBP), the latter of which is thought to reflect inflammation caused by endotoxemia.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Therefore, it remains unknown whether synbiotic administration definitely reduced plasma LPS levels in T2DM. Third, the detection rate (2.4%) of gut bacteria in blood was very low compared with a previous study (22.0%) [13]. Therefore, we could not evaluate the effects of the synbiotic on the translocation of live gut bacteria to the blood.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Therefore, it remains unknown whether synbiotic administration definitely reduced plasma LPS levels in T2DM. Third, the detection rate (2.4%) of gut bacteria in blood was very low compared with a previous study (22.0%) [13]. Therefore, we could not evaluate the effects of the synbiotic on the translocation of live gut bacteria to the blood.…”
Section: Discussionmentioning
confidence: 66%
“…Plasma lipopolysaccharide (LPS) from gram-negative bacteria, like translocation of gut bacteria, is an inflammatory mediator that contributes to insulin resistance [ 9 , 10 ]. Translocated LPS in the systemic circulation binds to LPS-binding protein (LBP), which is a marker for metabolic syndrome [ 11 , 12 ], and our previous study showed clear positive associations between plasma levels of interleukin-6 and LBP in patients with T2DM [ 13 ]. Furthermore, we found higher plasma LBP levels in T2DM patients with obesity and poor glycemic control [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 37 ] LPS translocation could be occurring in leaky gut syndrome. LPS could evoke strong systemic inflammation [ 38 , 39 ]. Increased gram-negative bacteria levels in the gut flora could increase LPS translocation.…”
Section: Discussionmentioning
confidence: 99%
“…LPS could evoke strong systemic in ammation. [38,39] Increased gram-negative bacteria levels in the gut ora could increase LPS translocation. Some past studies have reported that brain damage is related to gut dysbiosis or endotoxemia.…”
Section: Discussionmentioning
confidence: 99%